Sedimentary provenance and age of metamorphism of the Vestfold Hills, East Antarctica: evidence for a piece of Chinese Antarctica? - Clark, Chris; Kinny, Peter; Harley, Simon (Elsevier BV, 2012)
The Vestfold Hills terrane in East Antarctica is a granulite facies terrane that preserves a record of sedimentation, magmatism and metamorphism that differs significantly from the other Archaean terranes exposed in East Antarctica. Sensitive High Resolution Ion Mass Spectrometry (SHRIMP) U–Pb isotopic data from detrital zircon cores, metamorphic rims and metamorphic zircon and monazite from the granulite facies Chelnok and Taynaya Paragneisses that demonstrate Archaean ages that are incompatible with the established ages of other East Antarctic source regions. The original sediments to the Chelnok and Taynaya Paragneisses were deposited between c. 2575 and c. 2520 Ma and underwent a protracted period of high-grade granulite-facies metamorphism from c. 2520 to c. 2450 Ma that is synchronous with the emplacement of the tonalitic Mossel Gneiss and the granitic to gabbroic rocks of the Crooked Lake Gneiss Group. The distinctive detrital zircon age populations and the period metamorphism recorded by the Vestfold Hills paragneisses lead us to speculate that: (1) these rocks were sourced from, and deposited on the margin of the crystalline basement to the North China Craton at the end of the Archaean, and (2) they underwent a period of high-grade metamorphism related to orogenesis driven by the collision of the North China Craton with the Archaean nucleus of South India during the late-Archaean to early-Paleoproterozoic.